Sistema autônomo para inspeções visuais e termográficas em subestações de energia elétrica - Selson Carias Gomes Junior (2017)
To ensure the supply of electricity it is essential for utilities to maintain full operation of its assets, efficiently and optimally. To evaluate the operating conditions of the power substations' assets, thermographic inspections occur periodically, monitoring equipment's surface temperature looking for irregular operating conditions. Due to a number of factors, sometimes the frequency of inspections is less than adequate to ensure the detection of anomalies at the asset. Moreover, as all manual activity, it is difficult to standardize the execution, making room for failure. In order to present an alternative to these questions, this work detail the project, construction characteristics and laboratory validation of an autonomous system of thermal and visual inspection for electrical substations. This system moves on rails and performs scheduled inspections autonomously and collects information about the operating conditions of the assets in a standardized manner, significantly increasing the number of inspections of equipment. The tests showed that the system complies with the conditions proposed for its construction. All data is transmitted by the rails, as well as the electrical energy required for operation. The displacement tests indicate a maximum error of 6% in the inspection stop positions. The uncertainties associated to the thermographic inspection result have low variation, being higher in components with lower emissivity. The comparison with manual inspections shows that autonomous inspections performed by the system have satisfactory performance, accrediting the system as a solution to the problem of monitoring substation's assets.